High genome plasticity and frequent genetic exchange in Leishmania tropica isolates from Afghanistan, Iran and Syria. - Hedvig Glans; Maria Lind Karlberg; Reza Advani; Maria Bradley; Erik Alm; Björn Andersson; Tim Downing (PLoS Neglected Tropical Diseases, 2021)
Background The kinetoplastid protozoan Leishmania tropica mainly causes cutaneous leishmaniasis in humans in the Middle East, and relapse or treatment failure after treatment are common in this area. L. tropica's digenic life cycle includes distinct stages in the vector sandfly and the mammalian host. Sexual reproduction and genetic exchange appear to occur more frequently than in other Leishmania species. Understanding these processes is complicated by chromosome instability during cell division that yields aneuploidy, recombination and heterozygosity. This combination of rare recombination and aneuploid permits may reveal signs of hypothetical parasexual mating, where diploid cells fuse to form a transient tetraploid that undergoes chromosomal recombination and gradual chromosomal loss. Methodology/principal findings The genome-wide SNP diversity from 22 L. tropica isolates showed chromosome-specific runs of patchy heterozygosity and extensive chromosome copy number variation. All these isolates were collected during 2007-2017 in Sweden from patients infected in the Middle East and included isolates from a patient possessing two genetically distinct leishmaniasis infections three years apart with no evidence of re-infection. We found differing ancestries on the same chromosome (chr36) across multiple samples: matching the reference genome with few derived alleles, followed by blocks of heterozygous SNPs, and then by clusters of homozygous SNPs with specific recombination breakpoints at an inferred origin of replication. Other chromosomes had similar marked changes in heterozygosity at strand-switch regions separating polycistronic transcriptional units. Conclusion/significance These large-scale intra- and inter-chromosomal changes in diversity driven by recombination and aneuploidy suggest multiple mechanisms of cell reproduction and diversification in L. tropica, including mitotic, meiotic and parasexual processes. It underpins the need for more genomic surveillance of Leishmania, to detect emerging hybrids that could spread more widely and to better understand the association between genetic variation and treatment outcome. Furthering our understanding of Leishmania genome evolution and ancestry will aid better diagnostics and treatment for cutaneous leishmaniasis caused by L.tropica in the Middle East.